Quality and Freshness of Fish available in Super markets of Cochin, India based on Biogenic Amine content - Laly, S. J.; Anupama, T. K.; Ashok Kumar, K.; Sankar, T. V. (Fishery Technology, 2019)
Quality and freshness of thirty nine samples of freshand frozen fish sold in the super markets of Cochinwere determined in terms of biogenic aminecontent, biochemical and microbial parameters. Thecontents of putrescine, cadaverin, histamine, agmatine,tyramine, spermine and spermidine wereanalysed and it showed a wide variation with highercontent of spermine and cadaverine. Histaminecontent was less than 5 mg kg-1 (Range: Nd - 2.19±0.6mg kg-1). Putrescine, cadaverine, agmatine, tyramine,spermidine and spermine were in the range of Nd– 7.72±1.7 mg kg-1, Nd – 52.8 mg kg-1, Nd – 6.22mg kg-1, Nd – 4.34 mg kg-1, Nd - 51.8 mg kg-1 and0.21- 43.95 mg kg-1 respectively. Levels of putrescineand cadaverine were highest in Rastrelliger kanagurtaand Lethrinus nebulosus. In the present study 10.3%of samples exceeded Biogenic amine index (BAI)value of 20 mg kg-1. Around 7.7% of samples werehaving TVBN content more than 30 mg% and 10.3%of samples were having APC greater than or equalto 7 log cfu g-1. As indices based on biogenic aminesare not highly correlated with other quality indices,assessment of biogenic amine indices along withother quality indices for fresh fish can be recommended.